Screening, molecular docking and dynamic simulations of bioactive compounds from Prunus africana’s stem bark for potential prostate cancer inhibitors - Odozi , Nnenna Winifred; Osi, Valentine (Acta Chimica Asiana, 2025)
Prostate cancer is a major health problem for men, with few effective treatment choices. The growing interest in plant-based medicines needs more research into their safety and efficacy. In this study, twenty-seven (27) phytochemicals found in Prunus africana stem bark are evaluated using in silico methodologies such as toxicological and virtual screening, molecular docking, and molecular dynamics simulations. The PASS server projected that twenty (20) of these chemicals had anticancer properties. Molecular docking studies revealed that four bioactive compounds—β-Sitosterol (-8.9 kcal/mol), Campesterol (-8.7 kcal/mol), Prunetrin (-8.7 kcal/mol), and Stigmastan-3,5-diene (-8.7 kcal/mol)—have higher binding affinities than Flutamide (-8.6 kcal/mol), a commonly androgen receptor inhibitor. Further molecular dynamics simulations indicated that these compounds have comparable or greater stability than Flutamide. These data indicate that Prunus africana-derived phytochemicals could be viable candidates for prostate cancer treatment, necessitating further experimental validation.